Hubungan Kewenangan Pusat dan Daerah dalam Penyelenggaraan Otonomi Daerah Di Bidang Pendidikan Berdasarkan Undang-Undang Nomor 23 Tahun 2014 Tentang Pemerintahan Daerah - Andrea, Danetta Leoni (Kosmik Hukum, 2020)
The existence of the autonomous region gave birth to the relationship of authority between the Central Government with the regions. In this case, the relationship between the central authorities and the region will be discussed by the author is more specialize into the relationship of the authority in the field of education. Given that national education systems have an important role in feeding the nation of Indonesia considering also that at this time has entered the era of globalization, then the necessary higher education human resources capable of generating Indonesia quality in order to compete internationally. The existence of a connection between the central area can be seen from the governmental Affairs Division in the field of education which includes the management of education, curriculum, accreditation, educators and educational personnel, licensing education, as well as in terms of discussion and literature. As for the research methods used by the author is the juridical normative research, where the source of the data used is to use instrument-legal instruments related to local governance and National education systems as well as by using the results of the study of librarianship. Keywords: Education, The Relationship Of Authority, Regional Autonomy, Central Government, Regional Government.